Connecting Social: How Online Interactions Influence Social Support and Well-Being - Khansa Naira Larasati; Kunto Adi WIibowo; Detta Rahmawan (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2026)
This study examines the relationship between online interactions, social support, and psychological well-being among university students in Indonesia, with a specific focus on a public university, Universitas Padjadjaran. As online communication becomes an integral part of students’ daily lives, understanding its role in shaping social support and well-being is increasingly important. Using a quantitative survey method, data were collected from 121 undergraduate students through an online questionnaire employing a convenience sampling technique. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings indicate that online interactions have a significant positive effect on perceived social support. However, the direct effect of online interactions on psychological well-being and the mediating effect of social support on well-being were not statistically significant. These results suggest that while online interactions contribute to students’ perceptions of social support, their influence on psychological well-being may depend on additional contextual or individual factors. This study contributes to the growing literature on digital communication and well-being among university students in Indonesia.